Prospective Environmental Evaluation of Green Hydrogen Generation in the Colombian Northern Region Using Wind Energy and System Dynamics - Jeison Fernando Perlaza-Muriel; María Camila Rivas-Cifuentes; Nathaly Martínez Escobar; Juan Carlos Osorio-Gómez (Modelling and Simulation in Engineering)
With the signing of the Paris Agreement, which aims to limit global warming to 1.5°C by reducing greenhouse gas emissions and promoting climate adaptation, Colombia has demonstrated its commitment to the environment. This aligns with Sustainable Development Goals (SDGs) 7 and 13, which promote the use of sustainable energy and the reduction of CO2 emissions. Colombia’s decarbonization strategy, defined in the 2021 hydrogen roadmap, outlines how to implement low-emission hydrogen production to reduce GHG emissions by 2030. Considering Colombia’s wind potential, an analysis of hydrogen production in the Department of La Guajira using this renewable energy was conducted. System dynamics was used to represent the hydrogen production infrastructure from wind energy with a polymer electrolyte membrane (PEM) electrolyzer, considering the current and projected capacity of the wind farm. The results obtained from this simulation show a reduction in CO2 emissions compared to the baseline scenario. Five scenarios were explored to analyze the simulation results. The data revealed that from 2022 to 2050, CO2 emissions (kg) were reduced by between 5550 and 10,170. Additionally, the potential for hydrogen generation in the northern region of the country is highlighted, along with recommendations for decision-making related to production capacity.